CHILD CARE BEHAVIORS OF POSITIVE DEVIANCE FAMILY TO INCREASE CHILDREN NUTRITION STATUS IN SUMODIKARAN-DANDER-BOJONEGORO - Luthfia, Erien; Azizah, Nur (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2017)
Nutritional problem in childhood remains a serious problem in many countries. Positive deviance is a family-based approach that has a positive behavior that enables them to find better ways to prevent malnutrition.To reveal family behavioral child careexperience of positive deviance in improving the nutritional status of childhood.A qualitative approach with descriptive phenomenology design with the primary informants positive deviance family and supporters informant are non-positive deviance family, public health centre nutritional officers, and village midwives, taken through purposive sampling. Collecting data using in-depth interviews, FGD, observation and documentation study.Five core informants have participated in this study. Interviews were recorded and then made a transcript of the interview. Results of the study arethe primary caregiver is the mother assisted by other family members, the habit of being told and drinking milk before bed, the effort that the mother makes when the child is fussy with being seduced, invited to play, and not by force. Care of the child when sick with a more nutritious and favored child.The results of the study imply that good children care can reduce malnutrition. Need to increase the empowerment of families and share experiences among family Positive Deviance in efforts to improve the nutritional status of childhood.